Perjanjian Perkawinan Dalam Upaya Mencegah Perceraian Perspektif Hukum Islam : (Analisis Pasal 29 Undang – Undang Nomor 1 Tahun 1974) - Ali Qosim (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
The marriage agreement is an agreement made between the prospective spouses which regulates the rights and obligations between the prospective partners after the marriage occurs. The main problem in this thesis is how Islamic law views the content and existence of a marriage agreement before the marriage ceremony and how the effectiveness of the marriage agreement is in an effort to prevent divorce. The writing method in this thesis is a descriptive qualitative method using a type of library research, namely research that aims to be carried out by reading books and collecting data contained in rooms related to libraries, such as books, journals and materials related to problems in research and etc. Data and data sources used in this study are primary data sources, secondary data sources and tertiary data sources. Methods of data collection using the method of research literature and documentation.‎ What is the view of Islamic law regarding the contents and existence of a marriage agreement before the marriage ceremony is that the law of a marriage agreement is mubah law (permit), in the sense that not everyone who is about to get married must agree, there are also those who do not want to make an agreement. Meanwhile, the content of the marriage agreement is related to anything, as long as it does not violate legal boundaries. How is the effectiveness of a marriage agreement in an effort to prevent divorce, namely in making a marriage agreement that has benefits including avoiding divorce, for example a husband and wife make an agreement if there is a divorce, the agreement is that if there is a divorce, property belongs to a wife, therefore the husband does not divorce his wife because if the husband divorces his wife then nothing will get.